Development of techniques based on Monte Carlo simulations for clearance of Co-57 and Ge-68/Ga-68 sealed radioactive sources - Siarafera, Tatiana; Ntalla, Eleni; Mavrikis, Dimitris; Markopoulos, Angelos; Ioannidou, Alexandra; Savvidou, Anastasia (HNPS Advances in Nuclear Physics, 2019)
Sealed radioactive sources of Co-57 and Ge-68/Ga-68 are used for the calibration of various nuclear medicine systems like Gamma camera and PET imaging. After their useful life, these sealed sources need to be kept in control for decay until meeting the general clearance criterion. The aim of this work is to determine the activity of spent sealed radioactive sources of Ge-68 / Ga-68 and Co-57. For this purpose, techniques based on Monte Carlo simulation by the use of the MCNPX code was developed for evaluation of the 3”x3” NaI(Tl) scintillator efficiency for specific source–detector geometries. These techniques proved to be accurate.